2007
DOI: 10.1073/pnas.0611168104
|View full text |Cite
|
Sign up to set email alerts
|

Faithful modeling of transient expression and its application to elucidating negative feedback regulation

Abstract: Modeling and analysis of genetic regulatory networks is essential both for better understanding their dynamic behavior and for elucidating and refining open issues. We hereby present a discrete computational model that effectively describes the transient and sequential expression of a network of genes in a representative developmental pathway. Our model system is a transcriptional cascade that includes positive and negative feedback loops directing the initiation and progression through meiosis in budding yeas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 40 publications
1
47
0
Order By: Relevance
“…IME1 and IME2 are regulated through both positive-and negative-feedback loops (Rubinstein et al 2007;Ray et al 2013). To determine whether Rlm1 acts entirely upstream of IME1 vs. via feedback controls, we measured ime1D-lacZ expression in strains lacking functional Ime1 (i.e., ime1D-lacZ/ime1D), and we also measured ime2D-GFP expression in strains lacking functional Ime2 (i.e., ime2D-GFP/ime2D).…”
Section: Rlm1 Is Required For Early Meiotic Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…IME1 and IME2 are regulated through both positive-and negative-feedback loops (Rubinstein et al 2007;Ray et al 2013). To determine whether Rlm1 acts entirely upstream of IME1 vs. via feedback controls, we measured ime1D-lacZ expression in strains lacking functional Ime1 (i.e., ime1D-lacZ/ime1D), and we also measured ime2D-GFP expression in strains lacking functional Ime2 (i.e., ime2D-GFP/ime2D).…”
Section: Rlm1 Is Required For Early Meiotic Gene Expressionmentioning
confidence: 99%
“…Consistent with the ime1D-lacZ results, we found that ime2D-GFP/IME2 + strain expressed the fusion gene to higher levels in wild-type (RLM1 + ) colonies than in rlm1D colonies (Figure 2A, right). Thus, Rlm1 promotes transcription of both IME1 and IME2 in colonies.IME1 and IME2 are regulated through both positive-and negative-feedback loops (Rubinstein et al 2007;Ray et al 2013). To determine whether Rlm1 acts entirely upstream of IME1 vs. via feedback controls, we measured ime1D-lacZ expression in strains lacking functional Ime1 (i.e., ime1D-lacZ/ime1D), and we also measured ime2D-GFP expression in strains lacking functional Ime2 (i.e., ime2D-GFP/ime2D).…”
mentioning
confidence: 99%
“…Comparably, there are fewer mathematical studies of meiosis (Ray et al, 2013;Rubinstein et al, 2007;Shen et al, 2010) than mitosis in the literature; and among them, two mathematical models (Ray et al, 2013;Rubinstein et al, 2007) have been proposed to describe meiosis initiation. The most common feature of these two modelling studies is that both of them investigate the feedback loops involved in meiotic initiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the model restricts the protein/RNA expression level to a maximum value of nine which limits the protein and mRNA expression only to that threshold cutting off further expression ( Fig. 2A and Fig.3A in (Rubinstein et al, 2007)). Further, the weights for each edge are decided without considering the actual mechanisms and do not provide a detailed representation hindering the model's predictive capability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation